Responsabilidad de los padres, secreto profesional y confidencialidad médica. ¿Cómo se conjugan para asegurar la salud de los adolescentes - Kemelmajer de Carlucci, Aída (2012)
Parent’s responsibility, professional secrecy and medical confidentiality. How do they combine to ensure adolescentshealth?The article carefully analyzes the definition and content of professional secrecy and the right to privacy and introduces their implications on public and private policy. On that basis, main arguments in favor and against adolescents entitle to exercise the right to professional secrecy towards their representatives are presented. Finally, this article presents the existing case-law on that subject, provisions according the Ottawa Declaration and specific cases concerning professional secrecy exercise in the assumptions on termination pregnancy and HIV diagnosis.